Disturbance modeling and state estimation for offset-free predictive control with state-space process models - Tatjewski, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
Disturbance modeling and design of state estimators for offset-free Model Predictive Control (MPC) with linear state-space process models is considered in the paper for deterministic constant-type external and internal disturbances (modeling errors). The application and importance of constant state disturbance prediction in the state-space MPC controller design is presented. In the case with a measured state, this leads to the control structure without disturbance state observers.
Keywords: model predictive control; state-space models; disturbance rejection; state observer; Kalman filters